Peranan BMT Terhadap Pemberdayan Usaha Mikro: ( Studi Kasus BMT Al-Furqon Padang Sibusuk Kab. Sijunjung Prop. Sumatera Barat) - Arwin, Arwin (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2020)
The aim of this research is to explain the role of BMT in empowering micro businesses in the village / Nagari Padang Sibusuk Sijunjung West Sumatra. The role of BMT in providing financing opportunities for people to get financing as capital to open and develop micro businesses. This research is field research, while the data sources are obtained from observations, interviews, documentaries. While the data analysis used semi quantitative analysis. The results of this study regarding the role of BMT in empowering micro-businesses in Padang Sibusuk Village / Nagari, Kupitan District, Sijunjung Regency, West Sumatra are: One, the empowerment of Micro Enterprises in the field of micro business is growing rapidly. Two, the role of BMT Al-furqon Padang Sibusuk provides facilities in providing financing to increase the empowerment of Micro Enterprises in 2017 by 14.92 percent. In 2018 it was 24.76 percent and increased in 2019 to 38.73 percent. While at the macro level, the role of BMT Al-Furqon in Sijunjung Regency is 2.82 percent in 2017, 2.57 percent in 2018 and increased to 4.30 percent in 2019. Three, the HR BMT Al-furqon Padang Sibusuk also provides training and coaching to customers. micro business customers who can be financed from BMT Al-Furqon Padang Sibusuk.